Thermal stability of thiamine and its retention in canned sitao (Vigna sinensis va sesquipedialis Fruw.) during processing and storage - Mangona, Marietta Lopez
The thermal stability of thiamine in canned sitao during processing and storage was studied. Thermal destruction of thiamine in phosphate buffer (pH 5.0) and in sitao puree was followed by simple kinetic methods. Results gave good evidence that the reaction involved in the thermal destruction of thiamine follows a first order reaction rate over the temperature range studied. Thermal characteristics of thiamine were expressed in terms of D and z values. the Dr values obtained were 217.6 and 253.8 for phosphate buffer and sitao puree, respectively, while z values were 44.6 for phosphate buffer and 46.5 for sitao puree. results indicate that thiamine is more heat-resistant in the food product than in aqueous solutions. Thiamine losses during processing at 250°F were about 9% for the product packed in the bigger can size, 307 x 409 and 8% in the smaller size, 211 x 414. During storage at room and airconditioned temperatures, there was a decreasing trend in thiamine contents. After 6 months of storage, approximately 50% loss in thiamine was noted. Effects of can size can and temperature on thiamine loss during storage were found statistically insignificant. Results also showed that the reaction involved in the destruction of thiamine during storage follows a first order reaction rate at the two storage temperatures.